Impact of Strength Training Program on Physical Fitness and Psychical Condition for Elderly Women - Vaiva Abramavičiūtė; Kristina Zaičenkovienė (Lithuanian Sports University, 2018)
Research background and hypothesis. There is a lot of research proving that physical activity improves psychical condition when there are symptoms of psychical illness. There is also a wide range of studies carried out investigating the impact of physical activity on physical abilities, but little is known how strength training program as a factor improves psychical condition and, at the same time, body composition, strength and endurance for elderly woman. Research aim was to study the impact of an 8-week strength training program on physical fitness and psychical condition for elderly women. Research methods were literature review, HADS to evaluate anxiety and depression symptoms, anthropometry, strength and endurance testing, statistical analysis of physical fitness and psychical condition indices. Research results. In the period of 8-week strength training program we found that it had a positive impact on the indices in the experimental group compared to those in the control group. Psychical condition and strength results in experimental group were statistically significant (p  < 0.05); a significantly different change in aerobic endurance was measured during the 2 min step test. BMI and the body composition measures did not change statistically significantly. Discussion  and  conclusions. The  main  finding  is  that  an  8-week  strength  training  period  had  a  significant impact on psychical condition for elderly women. Moreover, strength training exercises improved upper and lower body muscle strength. Endurance improvement was observed during 2-min step test, but 6-min test results were insignificant (p > 0.05). After the 8-week training period, no significant differences in BMI and body composition were observed, although there was a slightly tendency of decrease in the experimental group. Keywords: elderly women, physical fitness, psychical condition, 8-week strength training programme, HADS, BMI.